A retrospective study of positive pressure ventilation in 58 dogs: indications, prognostic factors and outcome. (3rd April 2014) - Bruchim, Y.; Aroch, I.; Sisso, A.; Kushnir, Y.; Epstein, A.; Kelmer, E.; Segev, G.
<x xml:space="preserve">Abstract</x> OBJECTIVES To assess the usefulness of clinical and clinicopathological parameters as prognostic markers of survival in dogs undergoing positive pressure ventilation. METHODS Retrospective study of case records of 58 client‐owned dogs undergoing positive pressure ventilation. Dogs were divided into two groups; inadequate oxygenation due to pulmonary parenchymal disease (Group 1) and inadequate ventilation (Group 2). RESULTS Median duration of positive pressure ventilation was 30 (range 10 to 136) hours. Survival rate was 32% (19 dogs). Survivors were significantly younger (P<0·005) and had significantly higher (P<0·002) median PaO2/FiO2 ratio at 4 to 12 hours postinitiation of positive pressure ventilation, and immediately before weaning (P<0·006) compared to non‐survivors. A receiver operator characteristics analysis of PaO2/FiO2 immediately before weaning as predictor of survival had an area under the curve of 0·76 (95% confidence interval 0·54 to 0·97), with optimal cut‐off point of 252 mmHg, corresponding to a sensitivity and specificity of 0·80 and 0·79, respectively. The survival rates of dogs with PaO2/FiO2 less than 200 mmHg at 4 to 12 hours postinitiation of positive pressure ventilation, or immediately before weaning were 15% (3/20 dogs) and 6% (1/16 dogs), respectively. CLINICAL SIGNIFICANCE The PaO2/FiO2 ratio is an early prognostic indicator of successful weaning in dogs undergoing positive pressure ventilation.